2008
DOI: 10.1002/bit.22032
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic mineralization of pentachlorophenol (PCP) by combining PCP‐dechlorinating and phenol‐degrading cultures

Abstract: The dechlorination and mineralization of pentachlorophenol (PCP) was investigated by simultaneously or sequentially combining two different anaerobic microbial populations, a PCP-dechlorinating culture capable of the reductive dechlorination of PCP to phenol and phenol- degrading cultures able to mineralize phenol under sulfate- or iron-reducing conditions. In the simultaneously combined mixture, PCP (about 35 microM) was mostly dechlorinated to phenol after incubation for 17 days under sulfate-reducing condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…PCP is toxic to all forms of life, because it is an oxidative phosphorylation inhibitor (Yang et al 2009). Owing to its toxicity, widespread distribution and its impurities, PCP has been listed as a priority pollutant or restricted by the environmental protection agency (EPA) of USA and many other countries (e.g., dioxin, furans and hexachlorobenzene) (Cooper and Jones 2008;Dams et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…PCP is toxic to all forms of life, because it is an oxidative phosphorylation inhibitor (Yang et al 2009). Owing to its toxicity, widespread distribution and its impurities, PCP has been listed as a priority pollutant or restricted by the environmental protection agency (EPA) of USA and many other countries (e.g., dioxin, furans and hexachlorobenzene) (Cooper and Jones 2008;Dams et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the chemical concentrations used in the synthetic community in this study were much lower than those used in previous reports, i.e. 4 or 20 mM lactate, 20 mM FeO-OH, 20 mM SO 4 2- (Yang et al, 2009;Li et al, 2010Li et al, , 2013, and would avoid excessive resource consumption and decrease cost. Previous studies have reported the microbial degradation of 2,4,6-TBP aerobically or anaerobically (Ahn et al, 2003;Boyle et al, 1999;Uhnakova et al, 2009;Yamada et al, 2008).…”
Section: Mineralization Of 246-tbp By Combination Of Strain Ds Withmentioning
confidence: 93%
“…Due to predefined characteristics, the mineralization process did not cause any secondary byproducts, which improved the management and efficiency of the system, compared to the method of inoculating undefined, mixed cultures in previously reported mineralization systems, where most of the population in the community were not involved in the mineralization process. (Yang et al, 2009;Li et al, 2010Li et al, , 2013. Restricting such unnecessary microorganisms in the reaction mixture would increase the efficiency and achieve better control of the system.…”
Section: Mineralization Of 246-tbp By Combination Of Strain Ds Withmentioning
confidence: 99%
See 2 more Smart Citations